Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3310/hta18490
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre cluster randomised trial comparing a community group exercise programme and home-based exercise with usual care for people aged 65 years and over in primary care

Abstract: BackgroundRegular physical activity (PA) reduces the risk of falls and hip fractures, and mortality from all causes. However, PA levels are low in the older population and previous intervention studies have demonstrated only modest, short-term improvements.ObjectiveTo evaluate the impact of two exercise promotion programmes on PA in people aged ≥ 65 years.DesignThe ProAct65+ study was a pragmatic, three-arm parallel design, cluster randomised controlled trial of class-based exercise [Falls Management Exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
168
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(184 citation statements)
references
References 100 publications
6
168
1
3
Order By: Relevance
“…Trial participants performed below normative levels on most scales, except for Phone-FITT, PASE, CONFbal, and OPQOL; more details can be found in the HTA report. 9 The progress of practices and participants through the trial is shown in Figure 1. A total of 761 (61%) participants remained in the trial at the primary end-point 12 months after the end of the intervention period.…”
Section: Resultsmentioning
confidence: 99%
“…Trial participants performed below normative levels on most scales, except for Phone-FITT, PASE, CONFbal, and OPQOL; more details can be found in the HTA report. 9 The progress of practices and participants through the trial is shown in Figure 1. A total of 761 (61%) participants remained in the trial at the primary end-point 12 months after the end of the intervention period.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are no definitions of minimal clinically significant changes in FES-I or any other fear of falling measure, 25 our FES-I effect size is among the highest reported, with recent randomised studies on interventions in fear of falling using the FES-I reporting significant decreases in scores ranging from 0.53 to 3.7. [118][119][120] Dropouts from the study were at variable time points and tended to be triggered by activities arising from the study (e.g. example the CBTi in the intervention group).…”
Section: Summary Of Main Findings Of the Phase II Randomised Controllmentioning
confidence: 99%
“…(There is a wider debate and a separate body of evidence concerning strategies for the promotion of optimal physical fi tness (and, hence, falls prevention) at the population level, including the wider low-risk general population of 'fi t' older people (most notably by means of single-intervention tailored exercise programmes) 7,8 ).…”
Section: Scope and Purposementioning
confidence: 99%